Composite film based on sodium carboxymethyl cellulose and preparation method thereof
By optimizing the formulation ingredients in the composite membrane, adding starch, cellulose nanocrystals, tanninic acid, carnauba wax, antibacterial particles and modified diatomaceous earth-loaded sodium dehydroacetate, the problems of insufficient mechanical properties and poor antibacterial properties of the composite membrane are solved, and better application performance is achieved.
Patent Information
- Application Number
- CN202510103546.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-03-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the mechanical properties of the composite films are insufficient and the antibacterial properties are poor, which cannot meet the usage requirements.
Using a composite membrane based on sodium carboxymethylcellulose, the mechanical and antibacterial properties of the composite membrane are enhanced by optimizing the formulation ingredients, starch, cellulose nanocrystals, tanninic acid, carnauba wax, antibacterial particles and modified diatomaceous earth-loaded sodium dehydroacetate.
It significantly improves the mechanical properties and antibacterial properties of the composite film, making it suitable for food packaging and extends the shelf life of food.
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of polymer composite membrane materials, and in particular to a composite membrane based on sodium carboxymethyl cellulose and a preparation method thereof. Background Art
[0002] Sodium carboxymethyl cellulose is a modified natural cellulose, generally obtained by reacting natural cellulose with alkali and etherifying agent monochloroacetic acid. Its structural formula is similar to that of natural cellulose. Its physical properties include swelling when absorbing water, and forming a transparent viscous glue when swollen in water. It is relatively stable to light and room temperature, but is easily affected by bacteria, causing biodegradation, which affects its application. The sodium carboxymethyl cellulose in the prior art has the following main problems when preparing membrane materials: 1. There are a large number of hydrophilic hydroxyl groups and ionized carboxyl groups in sodium carboxymethyl cellulose, which affect its mechanical properties and further affect its application. 2. When used in food packaging, the antibacterial properties are poor and cannot meet the use requirements.
[0003] In order to solve one of the above problems, the prior art has also proposed many improved technical solutions, such as the Chinese patent application number CN202211268565.9, which discloses a biodegradable film and preparation method, and the raw materials are: 40-50 parts of polylactic acid particles, 20-25 parts of modified food-grade thermoplastic starch, 1-1.5 parts of nano titanium dioxide, 2-3 parts of sodium carboxymethyl cellulose, and 3.5-4.5 parts of tea tree essential oil. For example, the Chinese patent application number CN202210730052.9 discloses a method for preparing a degradable multifunctional food fresh-keeping packaging film, in which a certain mass of sodium carboxymethyl cellulose and polyvinyl alcohol, polyethyleneimine and a natural antibacterial factor mixture are prepared by a casting method. CMC-based film. Although they all have certain antibacterial properties, the direct addition of tea tree essential oil or natural antibacterial factors is easy to volatilize or lose during the preparation process, which will also lead to the problem of poor antibacterial properties of the film, and it does not play a positive role in mechanical properties. Summary of the invention
[0004] Based on this, in order to solve the problem that the mechanical properties of the composite membranes prepared in the prior art are insufficient and the antibacterial properties are poor, and the use requirements cannot be met, the present invention provides a composite membrane based on sodium carboxymethyl cellulose and a preparation method thereof, and the specific technical scheme is as follows: A composite film based on sodium carboxymethyl cellulose, the composite film comprising the following preparation raw materials in parts by weight: 45 to 50 parts of sodium carboxymethyl cellulose, 10 to 15 parts of starch, 5 to 9 parts of cellulose nanocrystals, 5 to 7 parts of tannic acid, 1 to 3 parts of carnauba wax, 1 to 12 parts of antibacterial particles, 1 to 3 parts of modified diatomaceous earth loaded with sodium dehydroacetate, and 1 to 2 parts of plasticizer; The antibacterial particles are prepared from quaternized xylan, wolfberry polysaccharide, nisin and nano zinc oxide in a mass ratio of (1-3):(1-5):(1-2):(1-3).
[0005] Furthermore, the degree of substitution of the sodium carboxymethyl cellulose is 0.5-1.2.
[0006] Furthermore, the preparation method of the antibacterial particles is: Add xylan to deionized water, stir at a speed of 1000 r / min~2000 r / min for 30 min~60 min, then add 2,3-epoxypropyltrimethylammonium chloride, and drop a sodium hydroxide solution of equal volume to deionized water, continue stirring for 3 h~4 h, cool to room temperature, add anhydrous ethanol, filter and collect the precipitate, wash, and dry at 60°C~70°C to obtain quaternized xylan; Add Lycium barbarum polysaccharide to deionized water to dissolve, then add nisin, stir continuously at a speed of 500 r / min~1000 r / min for 30 min~60 min, then centrifuge at a speed of 5000 r / min for 5 min~10 min, filter and take the filtrate; The quaternized xylan and nano zinc oxide are added to the filtrate, stirred at a speed of 100 r / min to 500 r / min for 20 min to 30 min, and spray-dried to obtain powdered antibacterial particles.
[0007] Furthermore, the addition ratio of the xylan to deionized water is (2-5) g / 10 mL; the mass ratio of the xylan to 2,3-epoxypropyltrimethylammonium chloride is 1:(2-3).
[0008] Furthermore, the addition ratio of the wolfberry polysaccharide to deionized water is (1-5) g / 10 mL.
[0009] Furthermore, the preparation method of the modified diatomite-loaded sodium dehydroacetate is: Dispersing diatomite in ethanol by ultrasonic, then adding a silane coupling agent, heating to 60°C to 70°C, stirring at a speed of 100 r / min to 150 r / min for 15 min to 30 min, to obtain modified diatomite; Sodium dehydroacetate is added to water and dissolved, and then the modified diatomaceous earth is added, stirred at room temperature for 5h~8h, and then placed in a freeze dryer for freeze drying. The freeze-dried product is then ground in a ball mill at a speed of 300r / min~500r / min for 1h~3h to obtain modified diatomaceous earth loaded with sodium dehydroacetate.
[0010] Furthermore, the volume ratio of the diatomaceous earth, ethanol and silane coupling agent is (1-3):(5-7):(3-5).
[0011] Furthermore, the mass ratio of the sodium dehydroacetate to the modified diatomaceous earth is (1-5):(5-9).
[0012] Furthermore, the plasticizer is at least one of glycerol, propylene glycol, diisononyl phthalate and epoxidized soybean oil.
[0013] In addition, the present invention also provides a method for preparing a composite film based on sodium carboxymethyl cellulose, the preparation method comprising the following steps: Slowly dissolve sodium carboxymethyl cellulose in deionized water, add plasticizer dropwise, heat to 75°C~100°C and stir magnetically for 30min~40min to obtain mixture A; Starch, cellulose nanocrystals, tannic acid and carnauba wax were mixed and ball-milled for 10 min to 15 min to obtain a mixture B; The mixture B is added to the mixture A, and stirred at a stirring speed of 200 r / min to 500 r / min for 20 min to 30 min, and then antibacterial particles and modified diatomaceous earth-loaded sodium dehydroacetate are added, and the mixture is stirred for 20 min to 30 min at 60° C. to 80° C. with the assistance of ultrasound to obtain a mixture C; The mixture C is prepared by a casting method to obtain a composite membrane.
[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses sodium carboxymethyl cellulose as a base film, and then optimizes the formula ingredients, adds starch, cellulose nanocrystals and tannic acid to generate interaction forces, can increase the crosslinking of the system, strengthen the matrix structure, and thus increase the mechanical properties of the composite film. With the help of carnauba wax, the smoothness of the composite film surface can be increased, and the plasticizer can increase the flexibility of the composite film. Then, by adding antibacterial particles, the high molecular sodium carboxymethyl cellulose group can carry the antibacterial group, giving the composite film significant antibacterial properties, and the modified diatomaceous earth loaded with sodium dehydroacetate also has a certain antibacterial effect. The synergistic effect not only makes the antibacterial property more excellent, but also can be interspersed in the composite film to increase the mechanical properties of the composite film, so that it has more excellent application performance, especially when applied to food packaging, while ensuring the mechanical properties of its application, it can also play an antibacterial effect, thereby extending the shelf life of the food.
[0015] 2. The present invention prepares antibacterial particles by compounding quaternized xylan, Lycium barbarum polysaccharide, nisin and nano zinc oxide in a specific ratio, and the components are synergistically enhanced to achieve a significant antibacterial purpose, and the antibacterial particles prepared by the present invention are not easy to lose during the composite film processing, and their antibacterial effect is relatively stable. Specifically, the present invention introduces quaternary ammonium salt cationic groups on the xylan main chain to give it more excellent antibacterial properties and biocompatibility, and the quaternary ammonium salt cationic groups are connected to the linear polymer skeleton in the system at the same time, and a certain load effect can be achieved, reducing the probability of active ingredients being lost during processing; Lycium barbarum polysaccharide has a broad spectrum of antibacterial, nisin has a significant inhibitory effect on bacteria, and Lycium barbarum polysaccharide has a highly branched structure and is rich in hydroxyl groups, which can significantly improve the use stability of nisin in the system, and combined with the sterilization activity of nano zinc oxide, the significant antibacterial purpose is achieved from multiple angles as a whole.
[0016] 3. The modified diatomaceous earth loaded with sodium dehydroacetate added in the present invention has excellent biocompatibility after modification, can be evenly dispersed in the network structure of sodium carboxymethyl cellulose, and simultaneously produce hydrogen bonding effect, further enhancing the mechanical properties of the composite film, and can also interact with antibacterial particles to effectively inhibit the growth of bacteria and molds, thereby extending the shelf life. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and do not limit the scope of protection of the present invention.
[0018] If no specific experimental steps or conditions are specified in the examples, all the experiments were carried out according to the conventional experimental steps or conditions described in the literature in the field. The reagents or instruments used without specifying the manufacturer are all conventional reagents that can be obtained commercially.
[0019] A composite film based on sodium carboxymethyl cellulose in one embodiment of the present invention comprises the following raw materials in parts by weight: 45 to 50 parts of sodium carboxymethyl cellulose, 10 to 15 parts of starch, 5 to 9 parts of cellulose nanocrystals, 5 to 7 parts of tannic acid, 1 to 3 parts of carnauba wax, 1 to 12 parts of antibacterial particles, 1 to 3 parts of modified diatomaceous earth loaded with sodium dehydroacetate, and 1 to 2 parts of plasticizer; The antibacterial particles are prepared from quaternized xylan, wolfberry polysaccharide, nisin and nano zinc oxide in a mass ratio of (1-3):(1-5):(1-2):(1-3).
[0020] In one embodiment, the degree of substitution of the sodium carboxymethyl cellulose is 0.5-1.2.
[0021] In one embodiment, the starch is tapioca starch.
[0022] In one embodiment, the preparation method of the antibacterial particles is: Add xylan to deionized water, stir at a speed of 1000 r / min~2000 r / min for 30 min~60 min, then add 2,3-epoxypropyltrimethylammonium chloride, and drop a sodium hydroxide solution of equal volume to deionized water, continue stirring for 3 h~4 h, cool to room temperature, add anhydrous ethanol, filter and collect the precipitate, wash, and dry at 60°C~70°C to obtain quaternized xylan; Add Lycium barbarum polysaccharide to deionized water to dissolve, then add nisin, stir continuously at a speed of 500 r / min~1000 r / min for 30 min~60 min, then centrifuge at a speed of 5000 r / min for 5 min~10 min, filter and take the filtrate; The quaternized xylan and nano zinc oxide are added to the filtrate, stirred at a speed of 100 r / min to 500 r / min for 20 min to 30 min, and spray-dried to obtain powdered antibacterial particles.
[0023] In one embodiment, the ratio of the added amount of xylan to deionized water is (2-5) g / 10 mL.
[0024] In one embodiment, the mass ratio of xylan to 2,3-epoxypropyltrimethylammonium chloride is 1:(2-3).
[0025] In one embodiment, the concentration of the sodium hydroxide solution is (0.1~0.3) mol / L.
[0026] In one embodiment, the addition ratio of the wolfberry polysaccharide to deionized water is (1-5) g / 10 mL.
[0027] In one embodiment, the preparation method of the modified diatomaceous earth loaded with sodium dehydroacetate is: Dispersing diatomite in ethanol by ultrasonic, then adding a silane coupling agent, heating to 60°C to 70°C, stirring at a speed of 100 r / min to 150 r / min for 15 min to 30 min, to obtain modified diatomite; Sodium dehydroacetate is added to water and dissolved, and then the modified diatomaceous earth is added, stirred at room temperature for 5h~8h, and then placed in a freeze dryer for freeze drying. The freeze-dried product is then ground in a ball mill at a speed of 300r / min~500r / min for 1h~3h to obtain modified diatomaceous earth loaded with sodium dehydroacetate.
[0028] In one embodiment, the volume ratio of diatomaceous earth, ethanol and silane coupling agent is (1-3):(5-7):(3-5).
[0029] In one embodiment, the mass ratio of the sodium dehydroacetate to the modified diatomaceous earth is (1-5):(5-9).
[0030] In one embodiment, the plasticizer is at least one of glycerol, propylene glycol, diisononyl phthalate and epoxidized soybean oil.
[0031] In addition, the present invention also provides a method for preparing a composite film based on sodium carboxymethyl cellulose, the preparation method comprising the following steps: Slowly dissolve sodium carboxymethyl cellulose in deionized water, add plasticizer dropwise, heat to 75°C~100°C and stir magnetically for 30min~40min to obtain mixture A; Starch, cellulose nanocrystals, tannic acid and carnauba wax were mixed and ball-milled for 10 min to 15 min to obtain a mixture B; The mixture B is added to the mixture A, and stirred at a stirring speed of 200 r / min to 500 r / min for 20 min to 30 min, and then antibacterial particles and modified diatomaceous earth-loaded sodium dehydroacetate are added, and the mixture is stirred for 20 min to 30 min at 60° C. to 80° C. with the assistance of ultrasound to obtain a mixture C; The mixture C is prepared by a casting method to obtain a composite membrane.
[0032] In one embodiment, the power of the ultrasonic assistance is 50W~100W, and the time is 5min~10min.
[0033] In one embodiment, the thickness of the composite film is 80 μm to 150 μm.
[0034] The composite film prepared by the above scheme has excellent mechanical properties and antibacterial properties, and can meet the application requirements in the field of food packaging.
[0035] The embodiments of the present invention will be described in detail below with reference to specific examples. Embodiment 1:
[0036] A composite film based on sodium carboxymethyl cellulose comprises the following raw materials in parts by weight: 48 parts of sodium carboxymethyl cellulose, 12 parts of cassava starch, 8 parts of cellulose nanocrystals, 5 parts of tannic acid, 2 parts of carnauba wax, 8 parts of antibacterial particles, 3 parts of modified diatomaceous earth loaded with sodium dehydroacetate and 2 parts of glycerol; The antibacterial particles are prepared from quaternized xylan, wolfberry polysaccharide, nisin and nano zinc oxide in a mass ratio of 2:3:1:2.
[0037] A method for preparing a composite film based on sodium carboxymethyl cellulose comprises the following steps: Add xylan to deionized water, and the addition ratio of the xylan to the deionized water is 5g / 10mL, stir at a speed of 1000r / min for 45min, then add 2,3-epoxypropyltrimethylammonium chloride, and the mass ratio of the xylan to 2,3-epoxypropyltrimethylammonium chloride is 1:2, and dropwise add a sodium hydroxide solution with an equal volume to the deionized water and a concentration of 0.2mol / L, continue stirring for 3h, cool to room temperature, add anhydrous ethanol, filter and collect the precipitate, wash, and dry at 65°C to obtain quaternized xylan; Add Lycium barbarum polysaccharide to deionized water to dissolve, and the addition ratio of Lycium barbarum polysaccharide to deionized water is 5g / 10mL, then add Nisin, stir continuously at a speed of 500r / min for 30min, then centrifuge at a speed of 5000r / min for 10min, filter and take the filtrate; Adding quaternized xylan and nano zinc oxide to the filtrate, stirring at a speed of 100 r / min for 25 min, and spray drying to obtain powdered antibacterial particles; The diatomite is ultrasonically dispersed in ethanol, and then a silane coupling agent is added, wherein the volume ratio of the diatomite, ethanol and the silane coupling agent is 1:5:3, and the mixture is heated to 65° C. and stirred at a speed of 150 r / min for 15 min to obtain modified diatomite; sodium dehydroacetate is added to water, dissolved, and then the modified diatomite is added, wherein the mass ratio of the sodium dehydroacetate to the modified diatomite is 3:7, and the mixture is stirred at room temperature for 5 h, and then the mixture is placed in a freeze dryer for freeze drying, and the freeze dried product is ground in a ball mill at a speed of 300 r / min for 2 h to obtain modified diatomite loaded with sodium dehydroacetate; Sodium carboxymethyl cellulose was slowly dissolved in deionized water, and glycerol was added dropwise, heated to 75°C and magnetically stirred for 30 minutes to obtain a mixture A; Cassava starch, cellulose nanocrystals, tannic acid and carnauba wax were mixed and ball-milled for 15 minutes to obtain a mixture B; The mixture B is added to the mixture A, stirred at a stirring speed of 200 r / min for 20 minutes, and then antibacterial particles and modified diatomaceous earth-loaded sodium dehydroacetate are added, and ultrasonic-assisted treatment is performed at 60° C. with a power of 50 W for 5 minutes, and stirring is continued for 20 minutes to obtain a mixture C; The mixture C was prepared by a tape casting method to obtain a composite film with a thickness of 100 μm. Embodiment 2:
[0038] A composite film based on sodium carboxymethyl cellulose comprises the following raw materials in parts by weight: 50 parts of sodium carboxymethyl cellulose, 10 parts of cassava starch, 9 parts of cellulose nanocrystals, 5 parts of tannic acid, 2 parts of carnauba wax, 8 parts of antibacterial particles, 3 parts of modified diatomaceous earth loaded with sodium dehydroacetate and 2 parts of glycerol; The antibacterial particles are prepared from quaternary ammonium xylan, wolfberry polysaccharide, nisin and nano zinc oxide in a mass ratio of 3:2:2:1.
[0039] A method for preparing a composite film based on sodium carboxymethyl cellulose comprises the following steps: Add xylan to deionized water, and the addition ratio of the xylan to the deionized water is 5g / 10mL, stir at a speed of 1000r / min for 50min, then add 2,3-epoxypropyltrimethylammonium chloride, and the mass ratio of the xylan to the 2,3-epoxypropyltrimethylammonium chloride is 1:2, and dropwise add a sodium hydroxide solution with an equal volume to the deionized water and a concentration of 0.2mol / L, continue stirring for 3h, cool to room temperature, add anhydrous ethanol, filter and collect the precipitate, wash, and dry at 70°C to obtain quaternized xylan; Add Lycium barbarum polysaccharide to deionized water to dissolve, and the addition ratio of Lycium barbarum polysaccharide to deionized water is 5g / 10mL, then add Nisin, stir at a speed of 500r / min for 35min, centrifuge at a speed of 5000r / min for 10min, filter and take the filtrate; Adding quaternized xylan and nano zinc oxide to the filtrate, stirring at a speed of 100 r / min for 30 min, and spray drying to obtain powdered antibacterial particles; The diatomite is ultrasonically dispersed in ethanol, and then a silane coupling agent is added, wherein the volume ratio of the diatomite, ethanol and the silane coupling agent is 2:5:3, and the mixture is heated to 70° C. and stirred at a speed of 150 r / min for 20 min to obtain modified diatomite; sodium dehydroacetate is added to water, dissolved, and then the modified diatomite is added, wherein the mass ratio of the sodium dehydroacetate to the modified diatomite is 5:9, and the mixture is stirred at room temperature for 7 h, and then the mixture is placed in a freeze dryer for freeze drying, and the freeze dried product is ground in a ball mill at a speed of 500 r / min for 2 h to obtain modified diatomite loaded with sodium dehydroacetate; Sodium carboxymethyl cellulose was slowly dissolved in deionized water, and glycerol was added dropwise, heated to 80°C and magnetically stirred for 35 minutes to obtain a mixture A; Cassava starch, cellulose nanocrystals, tannic acid and carnauba wax were mixed and ball-milled for 15 minutes to obtain a mixture B; The mixture B is added to the mixture A, stirred at a stirring speed of 250 r / min for 25 minutes, and then antibacterial particles and modified diatomaceous earth-loaded sodium dehydroacetate are added, and ultrasonic-assisted treatment is performed at 60° C. with a power of 50 W for 5 minutes, and stirring is continued for 20 minutes to obtain a mixture C; The mixture C was prepared by a tape casting method to obtain a composite film with a thickness of 100 μm. Embodiment 3:
[0040] A composite film based on sodium carboxymethyl cellulose comprises the following raw materials in parts by weight: 49 parts of sodium carboxymethyl cellulose, 11 parts of cassava starch, 8 parts of cellulose nanocrystals, 6 parts of tannic acid, 3 parts of carnauba wax, 8 parts of antibacterial particles, 3 parts of modified diatomaceous earth loaded with sodium dehydroacetate and 2 parts of glycerol; The antibacterial particles are prepared from quaternized xylan, wolfberry polysaccharide, nisin and nano zinc oxide in a mass ratio of 1:4:1:2.
[0041] A method for preparing a composite film based on sodium carboxymethyl cellulose comprises the following steps: Add xylan to deionized water, and the addition ratio of the xylan to the deionized water is 5g / 10mL, stir at a speed of 1000r / min for 60min, then add 2,3-epoxypropyltrimethylammonium chloride, and the mass ratio of the xylan to the 2,3-epoxypropyltrimethylammonium chloride is 1:3, and dropwise add a sodium hydroxide solution with an equal volume to the deionized water and a concentration of 0.2mol / L, continue stirring for 3h, cool to room temperature, add anhydrous ethanol, filter and collect the precipitate, wash, and dry at 65°C to obtain quaternized xylan; Add Lycium barbarum polysaccharide to deionized water to dissolve, and the addition ratio of Lycium barbarum polysaccharide to deionized water is 5g / 10mL, then add Nisin, stir continuously at a speed of 500r / min for 40min, then centrifuge at a speed of 5000r / min for 10min, filter and take the filtrate; Adding quaternized xylan and nano zinc oxide to the filtrate, stirring at a speed of 100 r / min for 30 min, and spray drying to obtain powdered antibacterial particles; The diatomite is ultrasonically dispersed in ethanol, and then a silane coupling agent is added, wherein the volume ratio of the diatomite, ethanol and the silane coupling agent is 3:7:4, and the mixture is heated to 65° C. and stirred at a speed of 150 r / min for 30 min to obtain modified diatomite; sodium dehydroacetate is added to water, dissolved, and then the modified diatomite is added, wherein the mass ratio of the sodium dehydroacetate to the modified diatomite is 4:7, and the mixture is stirred at room temperature for 6 h, and then the mixture is placed in a freeze dryer for freeze drying, and the freeze dried product is ground in a ball mill at a speed of 300 r / min for 3 h to obtain modified diatomite loaded with sodium dehydroacetate; Sodium carboxymethyl cellulose was slowly dissolved in deionized water, and glycerol was added dropwise, heated to 80°C and magnetically stirred for 40 minutes to obtain a mixture A; Cassava starch, cellulose nanocrystals, tannic acid and carnauba wax were mixed and ball-milled for 15 minutes to obtain a mixture B; The mixture B is added to the mixture A, and stirred at a stirring speed of 300 r / min for 30 minutes, and then antibacterial particles and modified diatomaceous earth-loaded sodium dehydroacetate are added, and ultrasonic-assisted treatment is performed at 65° C. with a power of 50 W for 5 minutes, and stirring is continued for 20 minutes to obtain a mixture C; The mixture C was prepared by a tape casting method to obtain a composite film with a thickness of 100 μm.
[0042] Comparative Example 1: The difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, sodium carboxymethyl cellulose is directly prepared by a conventional casting method to obtain a membrane material.
[0043] Comparative Example 2: The difference between Comparative Example 2 and Example 3 is that no tapioca starch is added in Comparative Example 2, and the other parts are the same as Example 2.
[0044] Comparative Example 3: The difference between Comparative Example 3 and Example 3 is that cellulose nanocrystals are not added in Comparative Example 3, and the rest is the same as Example 3.
[0045] Comparative Example 4: The difference between Comparative Example 4 and Example 3 is that tannic acid is not added in Comparative Example 4, and the rest is the same as Example 3.
[0046] Comparative Example 5: The difference between Comparative Example 5 and Example 4 is that no carnauba wax is added in Comparative Example 5, and the rest is the same as Example 3.
[0047] Comparative Example 6: The difference between Comparative Example 6 and Example 3 is that in Comparative Example 6, only quaternized xylan is added as the antibacterial particle, and the rest is the same as Example 3.
[0048] Comparative Example 7: The difference between Comparative Example 7 and Example 3 is that in Comparative Example 7, single Lycium barbarum polysaccharide is added as antibacterial particles, and the rest is the same as Example 3.
[0049] Comparative Example 8: The difference between Comparative Example 8 and Example 3 is that in Comparative Example 8, only nisin is added as the antibacterial particle, and the rest is the same as Example 3.
[0050] Comparative Example 9: The difference between Comparative Example 9 and Example 3 is that in Comparative Example 9, single nano zinc oxide is added as antibacterial particles, and the rest is the same as Example 3.
[0051] Comparative Example 10: The difference between Comparative Example 10 and Example 3 is that in Comparative Example 10, Lycium barbarum polysaccharide, nisin and nano zinc oxide are mixed to obtain antibacterial particles, and the rest is the same as Example 3.
[0052] Comparative Example 11: The difference between Comparative Example 11 and Example 3 is that no antibacterial particles are added in Comparative Example 11, and the rest is the same as Example 3.
[0053] Comparative Example 12: The difference between Comparative Example 12 and Example 3 is that diatomaceous earth is added in Comparative Example 12 to replace the modified diatomaceous earth to load sodium dehydroacetate, and the rest is the same as Example 3.
[0054] Comparative Example 13: The difference between Comparative Example 13 and Example 3 is that diatomaceous earth-loaded sodium dehydroacetate is added in Comparative Example 13 instead of modified diatomaceous earth-loaded sodium dehydroacetate, and the rest is the same as Example 3; The preparation method of diatomaceous earth-supported sodium dehydroacetate in Comparative Example 13 is as follows: Sodium dehydroacetate was added into water and dissolved, and then diatomaceous earth was added, and the mass ratio of the sodium dehydroacetate to the diatomaceous earth was 4:7. The mixture was stirred at room temperature for 6 hours, and then placed in a freeze dryer for freeze drying. The freeze-dried product was then ground in a ball mill at a speed of 300 r / min for 3 hours to obtain diatomaceous earth-loaded sodium dehydroacetate.
[0055] Comparative Example 14: The difference between Comparative Example 14 and Example 3 is that modified diatomaceous earth dehydrogenated sodium acetate is not added in Comparative Example 14, and the rest is the same as Example 3.
[0056] 1. Mechanical properties test: The composite film samples prepared in Examples 1 to 3 and the composite film comparison samples prepared in Comparative Examples 1 to 14 were subjected to performance tests, wherein the tensile strength and elongation at break were both referenced to GB / T13022-91, and the composite film samples in Examples 1 to 3 and the composite film comparison samples in Comparative Examples 1 to 14 were cut into rectangles of 8 cm in length and 3 cm in width, and measured using a spiral tension and compression dynamometer, with the initial fixture set to 50 mm and the speed set to 50 mm / min. The experiment was repeated 5 times and the average value was taken. The results are shown in Table 1 below.
[0057] Table 1: Performance test results Group Project Tensile strength / MPa Elongation at break / % Example 1 46.52±0.62 86.04±0.52 Example 2 47.05±0.75 87.11±1.23 Example 3 47.39±0.22 87.31±0.86 Comparative Example 1 6.1.23±1.35 13.31±1.04 Comparative Example 2 38.96±0.37 76.35±0.75 Comparative Example 3 36.15±1.02 71.23±1.12 Comparative Example 4 34.78±0.74 69.89±0.55 Comparative Example 5 43.89±1.35 81.25±1.04 Comparative Example 6 34.69±0.52 63.13±0.56 Comparative Example 7 38.24±0.75 74.11±0.76 Comparative Example 8 33.11±1.03 60.25±1.04 Comparative Example 9 35.08±0.68 64.86±0.88 Comparative Example 10 41.55±1.07 79.47±0.88 Comparative Example 11 29.19±0.72 55.17±1.06 Comparative Example 12 41.12±0.29 80.11±0.52 Comparative Example 13 39.55±1.22 79.07±0.75 Comparative Example 14 32.52±0.88 73.52±1.11 From the analysis of Table 1, it can be seen that the present invention can obtain a composite film with excellent tensile strength and elongation at break by optimizing the components, so that it meets the use requirements.Specifically, in Comparative Example 1, only sodium carboxymethyl cellulose was used to prepare the film, and its tensile strength and elongation at break were significantly worse than those in Example 3, and a smooth and delicate film could not be formed, and the film quality was poor; in Comparative Example 2, no cassava starch was added, and the tensile strength and elongation at break were also significantly worse than those in Example 3, and the film quality was poor, indicating that the addition of cassava starch in the present invention can increase the mechanical properties of the composite film and improve the uniformity and smoothness of the film; in Comparative Example 3, no cellulose nanocrystals were added, and the tensile strength and elongation at break were significantly worse than those in Example 3, indicating that the addition of cellulose nanocrystals can improve the mechanical properties of the composite film of the present application; in Comparative Example 4, no tannic acid was added, and the tensile strength and elongation at break were worse than those in Example 3, indicating that the addition of tannic acid in the present invention It can be used as a cross-linking modifier to increase the cross-linking of the composite film, which is helpful to improve the tensile strength and elongation at break of the composite film; in Comparative Example 5, no carnauba wax was added, and the surface smoothness of the composite film was significantly worse than that of Example 3, and the tensile strength and elongation at break were worse than those of Example 3, indicating that the addition of carnauba wax can promote the acquisition of a composite film with better quality; in Comparative Example 6, a single quaternized xylan was added. Since the quaternized xylan has excellent biocompatibility, it can interact with other components of the composite film to promote the formation of a composite film with a smooth and delicate surface, but its mechanical properties are worse than those of Example 3; in Comparative Example 7, a single wolfberry polysaccharide was added. Wolfberry polysaccharide has a highly branched structure and can produce hydrogen bonds with sodium carboxymethyl cellulose to promote the mechanical properties of the composite film, but The tensile strength and elongation at break of the single component were also worse than those of Example 3; in Comparative Example 8, a single nisin was added, and the tensile strength and elongation at break were significantly worse than those of Example 3; in Comparative Example 9, a single nano zinc oxide was added, which had a positive effect on the tensile strength and elongation at break, but the tensile strength and elongation at break of the single component were also worse than those of Example 3; in Comparative Example 10, only wolfberry polysaccharide, nisin and nano zinc oxide were added to obtain antibacterial particles, which could significantly promote the mechanical properties of the composite film, but the tensile strength and elongation at break were worse than those of Example 3; Comparative Example 11 did not add antibacterial particles, and its tensile strength and elongation at break were significantly worse than those of Example 3, indicating that the composite components of the present invention are used as antibacterial particles, which can significantly promote Improve the mechanical properties of the composite film; in Comparative Example 12, diatomaceous earth is added instead of modified diatomaceous earth loaded with sodium dehydroacetate. Diatomaceous earth can promote the mechanical properties of the composite film, but it has not been modified and is unevenly dispersed in the composite film, affecting the film quality, and its tensile strength and elongation at break are worse than those in Example 3; in Comparative Example 13, diatomaceous earth loaded with sodium dehydroacetate is added instead of modified diatomaceous earth loaded with sodium dehydroacetate. It has not been modified and its compatibility is not as good as that in Example 3, which affects the film-forming mechanical properties, making the tensile strength and elongation at break worse than those in Example 3; in Comparative Example 14, modified diatomaceous earth sodium dehydroacetate is not added, and the tensile strength and elongation at break are significantly worse than those in Example 3, indicating that the addition of modified diatomaceous earth sodium dehydroacetate has a positive effect on the mechanical properties of the composite film.
[0058] 2. Antibacterial property: Tested with reference to GB / T31402-2015, the composite film samples prepared in Examples 1 to 3 and the composite film samples prepared in Comparative Examples 1 to 14 were cut into 5 mm long and 5 mm wide specifications, sterilized with ultraviolet light, and placed in a 10 7 -10 8 In the center of the experimental plate of the colony, Escherichia coli and Bacillus subtilis were placed in an incubator at 36℃±1℃ for 24h; the mold was placed in an incubator at 28℃±1℃ for 72h, and the test was repeated 3 times to take the average value. The antibacterial activity was evaluated by comparing the size of the inhibition zone. The diameter of the inhibition zone / mm was tested in a constant temperature box at 25℃, and the results are shown in Table 2.
[0059] Table 2: Antibacterial effect test results Group strain Escherichia coli Bacillus subtilis Mold Example 1 19.20±0.20 25.20±0.30 35.70±0.10 Example 2 19.30±0.40 25.30±0.20 35.50±0.30 Example 3 19.50±0.30 25.40±0.40 35.80±0.20 Comparative Example 1 none none none Comparative Example 2 18.80±0.30 24.10±0.20 33.20±0.30 Comparative Example 3 19.10±0.20 25.10±0.30 35.10±0.30 Comparative Example 4 18.20±0.10 24.30±0.40 34.80±0.30 Comparative Example 5 18.90±0.30 25.10±0.50 35.30±0.20 Comparative Example 6 13.10±0.10 15.60±0.20 27.70±0.30 Comparative Example 7 13.50±0.30 17.30±0.30 26.10±0.20 Comparative Example 8 13.60±0.20 16.60±0.40 27.50±0.30 Comparative Example 9 13.30±0.20 15.70±0.30 28.40±0.30 Comparative Example 10 17.20±0.30 22.10±0.40 31.10±0.30 Comparative Example 11 9.20±0.30 10.70±0.40 14.20±0.10 Comparative Example 12 17.50±0.20 22.20±0.30 25.60±0.30 Comparative Example 13 18.80±0.20 24.60±0.10 34.70±0.20 Comparative Example 14 16.10±0.10 21.10±0.30 24.60±0.60 From the data analysis of Table 2, it can be seen that the present invention prepares antibacterial particles by adding compound quaternary ammonium xylan, wolfberry polysaccharide, nisin and nano zinc oxide, and the components synergistically enhance the effect, achieving a significant antibacterial purpose. In addition, by adding modified diatomaceous earth loaded with sodium dehydroacetate, synergistic antibacterial can also be achieved. Specifically, compared with Example 3, in Comparative Example 1, after sodium carboxymethyl cellulose is film-formed, it does not have antibacterial properties by itself; in Comparative Example 2, no cassava starch is added, which has a significant effect on the mechanical properties, but a general effect on the antibacterial properties; in Comparative Example 3, no cellulose nanocrystals are added, which has a general effect on the antibacterial properties; in Comparative Example 4, no tannic acid is added, which has a general effect on the antibacterial properties; in Comparative Example 5, no carnauba wax is added, which has a general effect on the antibacterial properties; Comparative Examples 6 to 10 are different in the composition of the antibacterial particles, but it can be clearly seen that the antibacterial properties are significantly reduced when a single component is used as an antibacterial particle, indicating that there is a synergistic effect between the antibacterial particles of the present invention, and the compound use achieves a more significant antibacterial effect; in Comparative Example 11, no antibacterial particles are added, and the antibacterial effect is significantly worse than that of Example 3, but because modified diatomaceous earth loaded with sodium dehydroacetate is also added to the system, it has a certain antibacterial effect, but The antibacterial effect still cannot meet the use requirements; in Comparative Example 12, diatomaceous earth is added to replace the modified diatomaceous earth to load sodium dehydroacetate. Since diatomaceous earth can be used as a filler in the preparation of the composite film, but it has not been modified, its dispersion degree is not good, and sodium dehydroacetate with antibacterial effect is not loaded, resulting in its antibacterial performance being worse than that of Example 3; in Comparative Example 13, diatomaceous earth is added to load sodium dehydroacetate instead of modified diatomaceous earth to load sodium dehydroacetate. Since it has not been modified, its dispersion effect and loading effect are not as good as those of Example 3, thereby making its antibacterial performance worse than that of Example 3; in Comparative Example 14, modified diatomaceous earth sodium dehydroacetate is not added, and the antibacterial performance is significantly worse than that of Example 3, especially the antibacterial effect of mold is significantly reduced, indicating that after adding modified diatomaceous earth sodium dehydroacetate, it can be evenly dispersed in the composite film, is more sensitive to the antibacterial effect of mold, and can also interact with the antibacterial particles to improve the antibacterial effect of the system. Therefore, based on the analysis of Table 1 and Table 2, it can be seen that the present application can not only promote the tensile strength and elongation at break of the composite film by optimizing the components, thereby ensuring the mechanical properties of its application, but also give the composite film significant antibacterial properties, thereby ensuring the antibacterial properties of its application.
[0060] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.
Claims
1. A composite film based on sodium carboxymethyl cellulose, characterized in that: The composite film comprises the following raw materials in parts by weight: 45 to 50 parts of sodium carboxymethyl cellulose, 10 to 15 parts of starch, 5 to 9 parts of cellulose nanocrystals, 5 to 7 parts of tannic acid, 1 to 3 parts of carnauba wax, 1 to 12 parts of antibacterial particles, 1 to 3 parts of modified diatomaceous earth loaded with sodium dehydroacetate, and 1 to 2 parts of plasticizer; The antibacterial particles are prepared from quaternized xylan, wolfberry polysaccharide, nisin and nano zinc oxide in a mass ratio of (1-3):(1-5):(1-2):(1-3).
2. The composite membrane according to claim 1, characterized in that The degree of substitution of the sodium carboxymethyl cellulose is 0.5-1.
2.
3. The composite membrane according to claim 1, characterized in that The preparation method of the antibacterial particles is as follows: Add xylan to deionized water, stir at a speed of 1000 r / min~2000 r / min for 30 min~60 min, then add 2,3-epoxypropyltrimethylammonium chloride, and drop a sodium hydroxide solution of equal volume to deionized water, continue stirring for 3 h~4 h, cool to room temperature, add anhydrous ethanol, filter and collect the precipitate, wash, and dry at 60°C~70°C to obtain quaternized xylan; Add Lycium barbarum polysaccharide to deionized water to dissolve, then add nisin, stir continuously at a speed of 500 r / min~1000 r / min for 30 min~60 min, then centrifuge at a speed of 5000 r / min for 5 min~10 min, filter and take the filtrate; The quaternized xylan and nano zinc oxide are added to the filtrate, stirred at a speed of 100 r / min to 500 r / min for 20 min to 30 min, and spray-dried to obtain powdered antibacterial particles.
4. The composite membrane according to claim 3, characterized in that The addition ratio of the xylan to deionized water is (2-5) g / 10 mL; the mass ratio of the xylan to 2,3-epoxypropyltrimethylammonium chloride is 1:(2-3).
5. The composite membrane according to claim 3, characterized in that The addition ratio of the wolfberry polysaccharide to deionized water is (1-5) g / 10 mL.
6. The composite membrane according to claim 1, characterized in that The preparation method of the modified diatomite-loaded sodium dehydroacetate is: Dispersing diatomite in ethanol by ultrasonic, then adding a silane coupling agent, heating to 60°C to 70°C, stirring at a speed of 100 r / min to 150 r / min for 15 min to 30 min, to obtain modified diatomite; Sodium dehydroacetate is added to water and dissolved, and then the modified diatomaceous earth is added, stirred at room temperature for 5h~8h, and then placed in a freeze dryer for freeze drying. The freeze-dried product is then ground in a ball mill at a speed of 300r / min~500r / min for 1h~3h to obtain modified diatomaceous earth loaded with sodium dehydroacetate.
7. The composite membrane according to claim 6, characterized in that The volume ratio of the diatomaceous earth, ethanol and silane coupling agent is (1-3):(5-7):(3-5).
8. The composite membrane according to claim 7, characterized in that The mass ratio of the sodium dehydroacetate to the modified diatomaceous earth is (1-5):(5-9).
9. The composite membrane according to claim 1, characterized in that The plasticizer is at least one of glycerol, propylene glycol, diisononyl phthalate and epoxidized soybean oil.
10. A method for preparing a composite film based on sodium carboxymethyl cellulose, characterized in that: The preparation method is used to prepare the composite film according to any one of claims 1 to 9, and the preparation method comprises the following steps: Slowly dissolve sodium carboxymethyl cellulose in deionized water, add plasticizer dropwise, heat to 75°C~100°C and stir magnetically for 30min~40min to obtain mixture A; Starch, cellulose nanocrystals, tannic acid and carnauba wax were mixed and ball-milled for 10 min to 15 min to obtain a mixture B; The mixture B is added to the mixture A, and stirred at a stirring speed of 200 r / min to 500 r / min for 20 min to 30 min, and then antibacterial particles and modified diatomaceous earth-loaded sodium dehydroacetate are added, and the mixture is stirred for 20 min to 30 min at 60° C. to 80° C. with the assistance of ultrasound to obtain a mixture C; The mixture C is prepared by a casting method to obtain a composite membrane.
Citation Information
Patent Citations
A method for preparing a biodegradable multifunctional food preservation packaging film
CN115109286B
Biodegradable film and preparation method thereof
CN115403909A
Marine degradable biomass plastic film and preparation method thereof
CN117362762A
Cited By
Epoxy modified starch-based degradable film and preparation method thereof
CN120137269A